Moonshots and the new industrial policy: Questioning the mission economy - Magnus Henrekson; Christian Sandström; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2024)
The notion that society should be organized around large so-called missions has gained momentum in public debate, and the reemergence of active industrial policy across the world has been inspired by academic scholars promoting the idea of Mission-Oriented Innovation Policies (MOIPs). The volume Moonshots and the New Industrial Policy: Questioning the Mission Economy provides a comprehensive assessment and normative critique of the efficacy of such policies. Besides the introductory chapter, it consists of 16 chapters distributed across three overarching themes: theoretical perspectives, empirical evidence, and alternative paths. This paper provides some additional analysis, pins down the most important general conclusions and suggests future research questions. Today's economies are highly dependent on a well-functioning process of decentralized experimentation, selection, and screening. Instead of large scale MOIPs, governments should strive to create an institutional framework that levels the playing field for potential entrepreneurs while encouraging productive entrepreneurship.
Keywords: H50; L26; L52; O31; O38; P16; 330; Mission-oriented policies; Innovation policy; New industrial policy; Moonshots; Rent seeking; Public choice